2001
DOI: 10.1089/107999001750133258
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 or Tumor Necrosis Factor-α Augmented the Cytotoxic Effect of Mycobacteria on Human Fibroblasts: Application to Evaluation of Pathogenesis of Clinical Isolates ofMycobacterium tuberculosisandM. aviumComplex

Abstract: Mycobacteria-induced in vitro events reflecting human tuberculosis can contribute to the evaluation of the pathogenesis of Mycobacterium tuberculosis (MTB). In this study, we propose such an in vitro method based on live mycobacteria-induced cytotoxicity to human cell lines. When human lung-derived normal fibroblast cell line MRC-5 was infected with various strains of mycobacteria (M. tuberculosis H(37)Rv and H(37) Ra, Mycobacterium avium 427S and 2151SmO, and Mycobacterium bovis BCG Pasteur and Tokyo), the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, a new method for PZA susceptibility testing is necessary. We have previously reported that viable M. tuberculosis H 37 Rv exhibits cytotoxicity to a human lung fibroblast cell line (19,20). As the cytotoxicity was counteracted by drugs, including isoniazide, rifampin, ethambutol, streptomycin, and PZA, a simple fibroblast cell-based assay (SFA) was developed to screen antimycobacterial drugs (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a new method for PZA susceptibility testing is necessary. We have previously reported that viable M. tuberculosis H 37 Rv exhibits cytotoxicity to a human lung fibroblast cell line (19,20). As the cytotoxicity was counteracted by drugs, including isoniazide, rifampin, ethambutol, streptomycin, and PZA, a simple fibroblast cell-based assay (SFA) was developed to screen antimycobacterial drugs (20).…”
mentioning
confidence: 99%
“…The human lung fibroblast cell line MRC-5 has been shown to be very sensitive to the cytotoxicity of live virulent bacilli of M. tuberculosis H 37 Rv, and the host cell viability was reflected by the state of the bacilli inside the host cells (19,20). As MRC-5 is a healthy diploid cell line, the cells are difficult to propagate for long periods.…”
mentioning
confidence: 99%
“…Gettler and el-Sadr7 reported activation of NTMI by carcinoma secondary to disruption of the granuloma either by cancer cells or by immune response to tumour antigens. Takii et al 11 found that interleukin 1 or tumour necrosis factor α augmented the cytotoxic effect of mycobacteria on human fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that human-lung-derived fibroblast MRC-5 cells are highly sensitive to mycobacterial cytotoxicity when compared to other human cell lines (32). The other host-cell-based methods using macrophages of either human or animal origin are documented (4,7,23,28), but the drawbacks of the use of macrophages derived from experimental animals is the heterogeneity of different batches of animal cells and consequent problems of reproducibility (21).…”
Section: Discussionmentioning
confidence: 99%
“…37 Rv exhibit cytotoxicity to human fibroblast cell line MRC-5. We have previously reported that among human cell lines, including U937 (monocyte), THP-1 (monocyte), HL-60 (myeloid), and A549 (lung epithelium), human lung fibroblast cell line MRC-5 is most susceptible to the cytotoxicity of virulent M. tuberculosis strain H 37 Rv, and this cytotoxicity is observed in live, but not dead, bacilli (32). When MRC-5 cells were cultured with live H 37 Rv bacilli, the cells were killed in a dose-dependent manner (Fig.…”
Section: Methodsmentioning
confidence: 99%